FORECASTING THE STAFFING NEEDS OF NATIONAL ECONOMIES AND THE IMPORTANCE OF THE FORMATION OF SCIENTIFIC AND EDUCATIONAL CLUSTERS - O. Demenko; E. Lopatin (Вестник университета)
This article discusses the need to design an innovative infrastructure that encompasses educational institutions, private and state-owned enterprises. Examples and prospects of creating an educational cluster in the oil and gas industry are given. The needs of the modern economic system in the workforce and the capabilities of the modern educational system in their satisfaction are analyzed. The higher school is considered as a set of scientific, production and educational basis. The importance of the formation of scientific and educational clusters in meeting the needs of modern economies is given. The scope of authors' research will be the sphere of forecasting the personnel market in conditions of modern reality and transition to a digital economy.